AgriTech4Kenya challenge: Innovations booklet 2025 - Wafullah, Teresah Nekesah; Khader, Taija Susanna; Loiseau, Camille (2025)
In June 2025, AgriTech4Kenya Demo Day concluded with a vibrant 𝗗𝗲𝗺𝗼 𝗗𝗮𝘆 𝗶𝗻 𝗡𝗮𝗶𝗿𝗼𝗯𝗶, where the 16 selected agri-tech startups showcased their innovative solutions to address Kenya’s most pressing food systems priorities, following the successful completion of a six-month acceleration program. Read more on the AgriTech4Kenya Innovation Challenge Cohort.